Kolaborasi BUMDes dan Program CSR dalam Pemberdayaan Masyarakat : Studi pada Petani Kopi di Desa Baloi, Kabupaten Murung Raya - Novri Amdani Saragih; Saputra Adiwijaya; Ida Bagus Suryanatha (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes community empowerment through the collaboration between the Village-Owned Enterprise (BUMDes) Baloi Usaha Mandiri and the Corporate Social Responsibility (CSR) program of PT Maruwai Coal in developing the local coffee commodity